2020
DOI: 10.17557/tjfc.831853
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT SOWING DATES ON THE GRAIN YIELD AND SOME YIELD CHARACTERISTICS OF TEFF [Eragrostis teff (Zucc.) Trotter]

Abstract: This research was carried out to determine the potential of teff as a staple crop for the Mediterranean climate during 2015 and 2016. The effects of four different sowing dates (15 April, 15 May, 15 June and 15 July) on the grain yield and some yield characteristics were investigated. The teff genotype "Dessie" was used as plant material and plant height, thousand-grain weight, harvest index and grain yield were tested. Two-year average results indicated that there were significant differences in mentioned cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
1
1
Order By: Relevance
“…In previous studies, herbage and hay yields were reported respectively as between 884-5275 kg da -1 and between 189-960 kg da -1 (Timuragaoglu et al, 2004;Sayar and Anlarsal, 2008;Sayar et al, 2009;Geren and Alan, 2012). Present findings were slightly lower than earlier findings since previous genotypes were sown in winter.…”
Section: Herbage and Hay Yieldscontrasting
confidence: 53%
“…In previous studies, herbage and hay yields were reported respectively as between 884-5275 kg da -1 and between 189-960 kg da -1 (Timuragaoglu et al, 2004;Sayar and Anlarsal, 2008;Sayar et al, 2009;Geren and Alan, 2012). Present findings were slightly lower than earlier findings since previous genotypes were sown in winter.…”
Section: Herbage and Hay Yieldscontrasting
confidence: 53%
“…Dev kralotu bitkisi üzerinde üç farklı biçim yüksekliğini (5, 10, 15 cm) test eden Paulino et al (2007), HP oranlarının biçim yüksekliğinden etkilenmediğini vurgulamıştır. Buna karşılık, Miscanthus x giganteus'da farklı biçim yüksekliğinin (0, 5, 10, 15, 20 cm) silaj HP oranı üzerinde önemli etkisini bildiren Geren et al (2019), 0 cm'den 20 cm'ye doğru artan anız yüksekliği karşısında HP oranlarının sırasıyla %6.6, 7.0, 7.5, 8.5 ve 9.6'ya yükseldiğini ifade etmişlerdir. Öte yandan, çok yıllık buğdaygillerde uygulanan biçim işlemleri sonucunda toprak yüzeyinde bırakılan anız miktarı ne kadar fazlaysa yaprak oranının da arttığını, sert yapılı, selülozca zengin sap oranı ne kadar az ise yemin HP oranının yükseldiğini ifade eden araştırıcılar, bulgularımızı desteklemektedir (Ishii et al, 1995;Can vd., 2003;Kuşvuran & Tansı, 2003).…”
Section: Discussionunclassified